COMBINING ABILITY ANALYSIS AND HETEROTIC STUDIES FOR WITHIN-BOLL YIELD COMPONENTS AND FIBRE QUALITY IN COTTON - I. Ali; A. Shakeel; A. Saeed; W. Nazeer; Z. U. Zia; S. Ahmad; K. Mahmood; W. Malik (Journal of Animal and Plant Sciences, 2016)
Combining ability and heterosis for within-boll yield components and fibre quality traits were carried out using line × tester mating system in upland cotton at the University of Agriculture, Faisalabad, Pakistan.Variance due to specific combining ability was greater than general combining ability for all the traits depicting the importance of non-additive genetic effects.The line BH-89 was found to be good general combiner for lint mass per boll, seed volume per 100 seeds, surface area per seed and lint percentage. NIAB-999 was good general combiner for fibre fineness. The third line which was actually the F1 of the first two lines performed better regardingseed number per boll, seed mass per bolland fibre strength.Among testers, NIAB-78 exhibited higher GCA effects for seed number per boll, lint mass per boll and fibre fineness while CIM-1100 proved to be good general combiner for seed volume per 100-seeds, surface area per seed and lint percentage. NIAB-999 × VH-144 exhibited the highest SCA effects regarding seeds per boll and seed mass per boll while the cross NIAB-999 × CIM-70 was considered desirable for seed volume per 100-seeds and surface area per seed. Maximum heterosis over better parent for lint mass per boll and lint percentage was observed for the cross BH-89 × NIAB-78 while for seed volume per 100-seeds and surface area per seed, NIAB-999 × CIM-240 was the best.
Keywords: Genetics; cotton; within-boll yield components; fibre quality